Clinical Analysis of the Treatment of Primary Trigeminal Neuralgia by Percutaneous Balloon Compression - Wang, Hui; Chen, Chunhui; Chen, Da; Li, Fengsheng; Hu, Shan; Ding, Wenqian; Wang, Jun; Chen, Wanghua (Frontiers in Surgery, 2022)
Purpose: To summarize the technical points and clinical effects of percutaneous balloon compression (PBC) in the treatment of primary trigeminal neuralgia. Methods: The clinical data of 13 patients with trigeminal neuralgia who received PBC from April 2020 to July 2021 were retrospectively analyzed. VAS, VRS-4 and PPI were used to evaluate the postoperative pain relief. Different postoperative complications were analyzed. Results: All patients had a smooth operation, the inflation volume of the balloon was 0.7ml, the average compression time was 120s, and there was no balloon rupture during the operation. On the day after operation, 12 patients (92.3%) had complete pain relief, and 1 patient (7.7%) was not satisfied with pain relief, but the pain disappeared 2 weeks after the operation. After operation, there were 12 patients with facial numbness in the affected side (92.3%), 3 patients with masseter muscle weakness (23.0%), 1 patient with herpes around the mouth (7.6%) and 1 patient with diplopia (7.6%). Conclusion: PBC is an effective minimally invasive surgical method for the treatment of primary trigeminal neuralgia. It is suitable for the elderly and infirm people, those who cannot tolerate general anesthesia or are afraid of surgery, and patients who had undergone surgery but relapsed after surgery. However, it is necessary to pay attention to the serious facial numbness and postoperative masticatory weakness. These discomforts are generally relieved after half a year.